Preliminary Evidence That CD38 Moderates the Association of Neuroticism on Amygdala-Subgenual Cingulate Connectivity - Tabak, Benjamin A.; Young, Katherine S.; Torre, Jared B.; Way, Baldwin M.; Burklund, Lisa J.; Eisenberger, Naomi I.; Lieberman, Matthew D.; Craske, Michelle G. (Frontiers in Neuroscience, 2020)
CD38 genetic variation has been associated with autism spectrum disorders and social anxiety disorder, which may result from CD38’s regulation of oxytocin secretion. Converging evidence has found that the rs3796863 A-allele contributes to increased social sensitivity compared to the CC genotype. The current study examined the moderating role of CD38 genetic variants (rs3796863 and rs6449182) that have been associated with enhanced (or reduced) social sensitivity on neural activation related to neuroticism, which is commonly elevated in individuals with social anxiety and depression. Adults (n=72) with varying levels of social anxiety and depression provided biological samples for DNA extraction, completed a measure of neuroticism, and participated in a standardized emotion processing task (affect matching) while undergoing fMRI. A significant interaction effect was found for rs3796863 x neuroticism that predicted right amygdala-subgenual anterior cingulate cortex (sgACC) functional connectivity. Simple slopes analyses showed a positive association between neuroticism and right amygdala-sgACC connectivity among rs3796863 A-allele carriers. Findings suggest that the more socially sensitive rs3796863 A-allele may partially explain the relationship between a known risk factor (i.e., neuroticism) and promising biomarker (i.e., amygdala-sgACC connectivity) in the development and maintenance of social anxiety and depression.